ANALISIS KONSENTRASI DAN SPESIASI LOGAM BERAT PADA PENGOMPOSAN LIMBAH LUMPUR IPAL DOMESTIK (Studi Kasus : IPAL Waduk Setiabudi, Jakarta Selatan) - Aryanti, Dini (Universitas Ibn Khaldun, 2018)
Sewage sludge generated from WWTP can be reused by composting because it contains a high organic content. However, the content of heavy metals in sewage sludge can be a major cause negative impacts on the environment and human health. The purpose of this study is to analyze the changes in the physical-chemical parameters, concentration and chemical speciation of Cu and Pb in two compost mixtures as an assessment of the feasibility of both composts to be used as fertilizer. The result showed that the parameters of temperature, pH, and C/N ratio in both compost met the standard quality of compost according to SNI 19-7030-2004. Concentration of Cu in compost 1 and compost 2 were 150 mg/kg and 237 mg/kg respectively, while the concentration of Pb were 224 mg/kg and 183 mg/kg respectively. The concentration of both metals in two composts resulted ecological risk factor that go into a low risk category (Er < 40). In addition, the composting process in this study reduced the toxicity effect of two metals. At the end of composting, fractions of Cu in two composts were dominant in organic bound fraction in amount of 63.50% for compost 1 and 56.20% for compost 2. While Pb were dominant in the residual fraction that is equal to 62.10% for compost 1 and 71.50% for compost 2. These fractions are the stable fracion so that the existence of Cu and Pb in two compost do not give negative impact to the environment if two composts will be applied to soil